2011
DOI: 10.1063/1.3515534
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydration reactions for “piano-stool” RAPTA-B and [Ru(η6− arene)(en)Cl]+ complexes: Density functional theory computational study

Abstract: The hydration process for two Ru(II) representative half-sandwich complexes: Ru(arene)(pta)Cl(2) (from the RAPTA family) and [Ru(arene)(en)Cl](+) (further labeled as Ru_en) were compared with analogous reaction of cisplatin. In the study, quantum chemical methods were employed. All the complexes were optimized at the B3LYP/6-31G(d) level using Conductor Polarizable Continuum Model (CPCM) solvent continuum model and single-point (SP) energy calculations and determination of electronic properties were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Stable stationary geometries were obtained for the four complexes which are characterized with zero imaginary number. The bond orders, ( ), and ∇ 2 ( ) of the Ru-Cl bonds increase in the hydrated complexes 2 and 4 which suggests that the possibility of displacing the last Cl atom with aqua ligand will be difficult [42]. The results from the NBO and NEDA analyses with the features HOMO and LUMO show that complexes 1 and 4 are predominantly characterised with LMCT while complexes 2 and 3 are predominately characterised with MLCT.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Stable stationary geometries were obtained for the four complexes which are characterized with zero imaginary number. The bond orders, ( ), and ∇ 2 ( ) of the Ru-Cl bonds increase in the hydrated complexes 2 and 4 which suggests that the possibility of displacing the last Cl atom with aqua ligand will be difficult [42]. The results from the NBO and NEDA analyses with the features HOMO and LUMO show that complexes 1 and 4 are predominantly characterised with LMCT while complexes 2 and 3 are predominately characterised with MLCT.…”
Section: Resultsmentioning
confidence: 95%
“…to the second optimization (−6307.84, −5925.61, −6464.26, and −6082.04 A.U.). The bond orders of the Ru-Cl bonds increase in the hydrated complexes 2 and 4 which suggest that the possibility of displacing the second Cl atom with aqua ligand will be difficult [42]. But on the other hand, the Ru-P bond order decreases upon hydration of the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the arene ligand has only marginal influence on the hydration reaction. In the first part of the study, two possible reaction mechanisms: associative and dissociative were compared and contrary to the hydration of the [Ru(η 6 −p‐cymene)(en)Cl] + complex studied previously, it was found that the examined process occurs with a higher probability via the dissociative mechanism in the Ru(II)‐quinolone complexes. This mechanism is linked with two transition states and one intermediate structure.…”
Section: Discussionmentioning
confidence: 95%
“…Density functional theory (DFT) approaches are now widely used to characterize the structure of novel antitumoral complexes. However, computational simulations are also able to assist the design of new molecules at an earlier stage, even prior to the design of the synthetic route . Indeed, one can easily find in the literature excellent theoretical works to anticipate the structures, optical properties, and/or biochemical activities of novel drugs. We have contributed to this field by using theoretical approaches to predict the cytotoxicity of drugs containing transition metals in their structures. …”
Section: Introductionmentioning
confidence: 99%